People Aged Over 75 in Atrial Fibrillation on Warfarin: The Rate of Major Hemorrhage and Stroke in More Than 500 Patient-Years of Follow-Up - Johnson, Christina E.; Lim, Wen K.; Workman, Barbara S. (Journal of the American Geriatrics Society (JAGS), 2005)
Objectives: To determine the incidence of major hemorrhage and stroke in people aged 76 and older with atrial fibrillation on adjusted‐dose warfarin who had been recently been admitted to hospital. Design: A retrospective observational cohort study. Setting: A major healthcare network involving four tertiary hospitals. Participants: Two hundred thirty‐five patients aged 76 and older admitted to a major healthcare network between July 1, 2001, and June 30, 2002, with atrial fibrillation on warfarin were enrolled. Measurements: Information regarding major bleeding episodes, strokes, and warfarin use was obtained from patients, relatives, primary physicians, and medical records. Results: Two hundred twenty‐eight patients (42% men) with a mean age of 81.1 (range 76–94) were included in the analysis. Total follow‐up on warfarin was 530 years (mean 28 months). There were 53 major hemorrhages, for an annual rate of 10.0%, including 24 (45.3%) life‐threatening and five (9.4%) fatal bleeds. The annual stroke rate after initiation of warfarin was 2.6%. Conclusion: The rate of major hemorrhage was high in this old, frail group, but excluding fatalities, resulted in no long‐term sequelae, and the stroke rate on warfarin was low, demonstrating how effective warfarin treatment is.